Analysis of the Financial Capability of the Semarang City Regional Government over the Period 2018- 2022 - Shofaturrahmah, Putri Dini; Daroini , Selamet; Digdowiseiso , Kumba (CV ODIS, 2024)
Regional autonomy gives regions full authority to regulate and manage the resources they have. However, to ensure independence, effectiveness and efficiency in the management of Semarang City regional finances by the Semarang City Regional Financial Agency, it is necessary to establish clear standards or guidelines. This research aims to evaluate the regional financial capacity of Semarang City from the 2018 to 2022 Fiscal Year using various financial ratio analyzes. The analysis includes financial capability ratios (Degree of Fiscal Decentralization), financial effectiveness ratios, financial efficiency ratios, and financial independence ratios. The results of this research show that the regional financial capacity of Semarang City during the 2018-2022 Fiscal Year period, although experiencing fluctuations, still shows a level of financial effectiveness that is in the effective and balanced effective category. Even though there was a decline in 2019 and 2021, the decline did not exceed 15%, it still remains in the balanced effective category, and an increase of above 5% is also included in the effective category. Semarang City's financial efficiency in 2018-2019 is classified as inefficient with an efficiency level above 100%. However, from 2020 to 2022, there will be a change to the efficiency category with an efficiency level below 100%. Semarang City's regional financial independence, although experiencing fluctuations, remains in the delegative category. The increase in the regional financial capacity of Semarang City from the 2018 to 2022 Fiscal Year based on the Degree of Fiscal Decentralization analysis shows an increase of more than 1% each year